Household Member Arrest and Adolescent Substance Use: The Mediating Roles of Parenting and Youth Psychological Distress. (August 2019) - Johnson, Elizabeth I.; Kilpatrick, Tanner; Bolland, Anneliese C.; Bolland, John
Using data ( N = 1, 803) from the Mobile Youth Survey, a community-based study of risk and resilience among predominantly African American youth, this study examines whether indicators of parenting and youth psychological distress mediate the relationship between household member arrest and substance use. Results of structural equation analyses suggest that household member contact with the criminal justice system has indirect effects on adolescent substance use via its impact on parenting. Household member arrest was associated with fewer family rules, monitoring, and curfew restrictions, which in turn was associated with increased frequency of alcohol and marijuana use. Although household member arrest was positively associated with psychological distress, there was no evidence of an internalizing pathway to substance use. Findings underscore the importance of identifying and then intervening on family processes as a way to reduce the impact of family contact with the criminal justice system on young people.